2021
DOI: 10.1103/physreva.104.033102
|View full text |Cite
|
Sign up to set email alerts
|

Extended quantitative rescattering model for simulating high-order harmonic streaking spectra by synchronization of an intense IR laser and a time-delayed attosecond XUV pulse

Abstract: We theoretically investigate the modulated high-harmonic generation (HHG) driven by an intense few-cycle infrared (IR) laser field and a weak extreme-ultraviolet (XUV) pulse at a delayed time. We establish an extended quantitative rescattering (EQRS) model to simulate the HHG streaking spectra, with the ideas of correcting the IR ionization and the transition from the ground to continuum states in the strong-field approximation.The EQRS model has an accuracy comparable to that from "exactly" solving the time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Different from most retrieval algorithms used for attosecond photoelectron streaking experiments, our method does not rely on the iterative procedure, thus errors in the retrieved results are introduced only by the experimental measurements and the model itself, but not by the convergence of the iterations. Note that, compared to the earlier retrieval method in [55], a significant advance has been made in the present version such that the spectral phase of any form can be directly extracted from the HHG spectra, even for the irregularly behaved phase. We showed that our method can well retrieve the spectral phases (or the temporal intensity profiles) for both isolated XUV and SXR pulses, which have a narrow bandwidth in the XUV and a broad bandwidth in the SXRs, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Different from most retrieval algorithms used for attosecond photoelectron streaking experiments, our method does not rely on the iterative procedure, thus errors in the retrieved results are introduced only by the experimental measurements and the model itself, but not by the convergence of the iterations. Note that, compared to the earlier retrieval method in [55], a significant advance has been made in the present version such that the spectral phase of any form can be directly extracted from the HHG spectra, even for the irregularly behaved phase. We showed that our method can well retrieve the spectral phases (or the temporal intensity profiles) for both isolated XUV and SXR pulses, which have a narrow bandwidth in the XUV and a broad bandwidth in the SXRs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate single-atom HHG streaking spectra under a linearly polarized weak XUV (or SXR) IAP and a strong IR (or MIR) laser, we can employ the previously established EQRS model [55]. This model is an improvement of SFA [56].…”
Section: Eqrs Modelmentioning
confidence: 99%
See 3 more Smart Citations